Climate securitization and Iraq's climate challenges (قضايا سياسية, 2024)
After the expansion of the concept of security since the end of the Cold War, it is no longer limited to state security related to military affairs only due to the emergence of other challenges and threats. One of the schools that studied the concept of contemporary security is the Copenhagen School of Security Studies, which presented a new concept in the issues that fall under the umbrella of security. Realizing that it is no longer possible, in light of the various challenges occurring in the world, to limit the dynamics of security only to military and political relations, the main focus of the Copenhagen School was the theory of securitization based on the premise that any issue in international relations can be securitized as long as that issue poses an existential threat to the survival of the world. An entity, but there are stages that the issue goes through, leading to the stage of securitization, and certain conditions and elements that must be met in that issue in terms of the position of the security actor, the security discourse, and the public. We analyzed the issue of climate change according to the assumptions of securitization theory, and there are four factors that contributed to the politicization of the climate issue, which is consensus. Scientific and the role of politics regarding climate change, financial financing, and international organizations, which we will discuss later. Iraq is among the countries most affected by climate change and environmental degradation, and especially the climate change crisis is increasing day after day in a very large way and is worsening in light of government measures that are very weak and do not rise to the occasion. Transform into real measures to confront a major security threat that threatens food security, water security, energy security, and societal security.